Exploring income-based disparities in plant based protein consumption: Evidence from indonesia using probit analysis - Nandiroh Umi; Khoiriyah Nikmatul; Forgenie David; Sa’diyah Ana Arifatus (BIO Web of Conferences)
In light of the global shift towards sustainable dietary patterns, this study investigates the influence of income on the consumption of plantbased proteins, namely tofu and tempeh, in Indonesia. This research uses probit regression analysis to examine the probability of consumption relative to income levels and household sizes among diverse demographic segments. Data from a nationally representative survey indicate that income significantly affects dietary choices, with higher-income households exhibiting varied likelihoods of consuming tofu and tempeh. The study finds that household size inversely affects tofu consumption, particularly among the affluent, while tempeh’s consumption is less sensitive to income and household size variations. These results underscore the complex interplay between economic status and food choices, with implications for policy measures to promote nutritional equity. Recommendations include price stabilization for tofu to ensure affordability across income strata and targeted educational campaigns to enhance awareness of tempeh’s nutritional benefits. The study contributes to the discourse on addressing dietary disparities and enhancing public health nutrition in a developing country.